SPECTROPHOTOMETRY APPLICATION FOR THE MONTMORILLONITE CONTENT DETERMINATION IN MOULDING SANDS WITH BENTONITE (Metallurgy and Foundry Engineering, 2011)
The theoretical bases of spectrophotometry used in analysis are discussed in the paper as well as the results of investigations of the montmorillonite content by means of the spectrophotometric adsorption of the Cu(II)-triethylenetetramine (Cu-TET) complex are presented. Bentonites originated from various producers (Sud Chemie, ZGM Zębiec S.A,) as well as samples of model moulding sands bonded by these bentonites were inwestigated in respect of their montmorillonite content. The montmorillonite content was measured in samples being at a room temperature and at temperatures of 400 °C and 700 °C. It was indicated, that the determined montmorillonite content in bentonite for the bentonites under investigation and for the model moulding sands with bentonites, are comparable, which proves that the quartz matrix, does not disrupt the measuring methodology and the applied spectrophotometric method is suitable for the moulding sands. It was found that at a temperature of 700 °C montmorillonite undergoes deactivation in the tested bentonites.